Electrophysiology of the mammalian cytoskeleton - Cantiello, Horacio Fabio (2024)
The cell's cytoskeleton consists of a dynamic structure containing actin-based filaments (F-actin),tubulin-based microtubules (MTs) and intermediate filaments. While it is well-known for maintaining cell shape and providing mechanical support, these cytoskeletal elements also have important electrical properties that may play a crucial role in electrical signaling and information processing within the cell. F-actin and MTs possess a large uncompensated charge, which give rise to nonlinear electrical properties, explaining the high sensitivity of cells to electric fields both in vitro and in vivo. Remarkably, the polymers of the cytoskeleton enable the generation of ionic condensation-based waves in F-actin and exhibit behavior analogous to transistors in MTs. This review summarizes three decades of research from our laboratory, elucidating the fundamentals and methodologies of cytoskeletal electrophysiology. The electrophysiology of the cytoskeleton is an emerging field of study that investigates the electrical properties and behavior of the various elements of the cytoskeleton and their implications for various areas of biology and medicine. The electrical properties of the cytoskeleton contribute to a new paradigm of cell physiology. They might be implicated in cell signaling and regulation, and associated with the sensory properties of the cell.